Trade in Live Music Services Between French Caribbean EU Territories and Anglophone CARIFORUM - Gordon, Lisa (My University, 2020)
The study assesses the state of trade in live music services between two regions: Guadeloupe; a French EU Caribbean territory and Trinidad & Tobago, an Anglophone CARIFORUM country. One of the reasons the research is salient is because it includes an examination of the efficacy of the EU-CARIFORUM Economic Partnership Agreement (2008); the first international trade accord exclusive to both regions. The study relied on sourcing primary data on this trade due to the paucity of secondary data. 61 music stakeholders were surveyed via a questionnaire structured around the four modes of trade as defined in the General Agreement of Trade in Services (GATS). Of these modes, modes IV and II have been historically associated with live music. Mode IV- (movement of natural persons) has been traditionally the primary method used in trade in cultural services between developing countries (of which CARIFORUM is a part) and other regions. Similarly, Mode II (consumption abroad) is a key transactional method of live music and a driver of FEX/Export markets, exemplified by the proliferation of festivals in both regions. Hence, a study on the trade performance of live music between Guadeloupe (EU) and Trinidad and Tobago (CARIFORUM) is critical for both regions. The methodology required a study of the following variables: demand, technology, trade facilitation, geographic proximity, legal institutions, and culture. They were examined within the framework of the Linder hypothesis of international trade. Sampling adequacy measurements such as the Kaiser-Meyer-Olkin (KMO) and Cronbach Alpha, were used to test the reliability and validity of the survey. Data analysis employed regression methods and a comparative examination of aggregates for each country. Key findings revealed that four variables had a positive impact on this trade. Geographical closeness was both significant and positive. Trade facilitation efforts had a positive effect as did technology and demand patterns.
Keywords: Music trade -- Caribbean Area; Caribbean Area -- Commerce; International relations; Economic Partnership Agreement; Cultural and creative industries